Neviditelná krajina v Nezvalově poezii 20. let - Čolakova, Žoržeta (Bohemistyka, 2018)
What is noticeable in the 1920s, when Czech modern poetry and Vítězslav Nezval in particular express their avant-garde quests through the felicitous poetic program, is the aesthetic distancing from the romantic melancholy and respectively from the interpretation of landscape as an object of contemplation and a mediator between the human soul and the universe. The preference of poetism for civilization diversity and metropolitan dynamics and its superficial disregard for nature are the reasons why this aspect of Vítězslav Nezval’s poetry has remained outside the field of literary research so far. The main objective of this paper is to discover and outline the manifestations of artistic treatment of nature in Nezval’s poetry even when he denies its place in modern poetry in general. The paper focuses on those transformational processes of anti-mimetic nature through which the image of the landscape is no longer perceived as a reflection of the real entities of nature but as a fictional entity based on the principle of collage.